Classification and Localization of Mixed Sources Using Uniform Circular Array under Unknown Mutual Coupling - Wang, Kai; Wang, Ling; Xie, Jian; Tao, Mingliang (Společnost pro radioelektronické inženýrství, 2019)
In this paper, the authors propose an effective classification and localization algorithm of mixed far-field and near-field sources using a uniform circular array under the unknown mutual coupling. In practice, the assumption of an ideal receiving sensor array is rarely satisfied. The effects of unknown mutual coupling would degrade the performance of most high resolution algorithms. Firstly, according to rank reduction type method, the direction of arrival of far-field sources is estimated directly without mutual coupling elimination. Then, these estimates are adopted to reconstruct the mutual coupling matrix. Finally, both direction and range parameters of near-field sources are obtained through MUSIC search after mutual coupling effects and far-field components elimination. The proposed algorithm only requires the second order cumulant and any three dimensional spectrum search is circumvented. Some simulation results would prove that the proposed algorithm can reduce more than eighty percent estimating error of mixed sources localization compared to those algorithms without mutual coupling compensation.
Keywords: Uniform circular array; direction of arrival; far-field; near-field; mutual coupling